(3QSGdI aj GdSjQI GdfHhjIs - (3eLghds ((3eSLOj GdYeGQI YfO bHQ GdeQMhe aGjb HGTGs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfTC GdYGde ef GdYOe CeG HYO aEfj CQOJ CPcQ CUd GdfHj ChdG hKGfjG hcjajI ehdOg heHYKg hXghQg hThcJg hHYV eYLRGJgs
(3BNQgG (B:s
(3aYdjfG GdUHQ cd faS PGFbI GdehJ heG cGf dfaS Cf JehJ EdG HEPf Gddg cJGHG eDLdG hef jQO KhGH GdOfjG fDJg efgG hef jQO KhGH GdBNQI fDJg efgG hSfLRj GdTGcQjfs
(3aj Chdg fbhd aj Gdabg dCHj GdSYhO, hCHjGJ TYQ hfbhd aj GdMOjK dGHf ceGd hdCHj GdaJM GdHSJjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJGQjNs